1996
DOI: 10.1161/01.cir.93.4.753
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Significance of Multiple Consecutive, Appropriate, High-Energy Discharges in Patients With Implanted Cardioverter-Defibrillators

Abstract: In patients with an ICD, the development of MCD is an independent predictor of cardiac and arrhythmic mortality. If this finding is confirmed in larger studies, it may help to identify patients in whom other therapeutic alternatives, ie, heart transplantation, should be considered during follow-up after ICD implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
86
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 61 publications
8
86
3
Order By: Relevance
“…[1][2][3] More specifically, electrical storm (ES), characterized by very frequent arrhythmic episodes resulting in appropriate ICD shocks, 4 is a frightening event associated with poor short-and long-term prognoses. [5][6][7][8][9][10][11][12][13][14] Although radiofrequency catheter ablation (CA) has an established role in the treatment of recurrent VT, 4,15 its value in patients with ES has been investigated only in selected series as a bailout therapy. 16 -18 …”
mentioning
confidence: 99%
“…[1][2][3] More specifically, electrical storm (ES), characterized by very frequent arrhythmic episodes resulting in appropriate ICD shocks, 4 is a frightening event associated with poor short-and long-term prognoses. [5][6][7][8][9][10][11][12][13][14] Although radiofrequency catheter ablation (CA) has an established role in the treatment of recurrent VT, 4,15 its value in patients with ES has been investigated only in selected series as a bailout therapy. 16 -18 …”
mentioning
confidence: 99%
“…[33][34][35] Although, recent clinical trials have suggested role of catheter ablation techniques as a first line treatment for electrical storm, antiarrhythmic drugs still remain the cornerstone for the therapy for electrical storm. Reversal of precipitating factors, optimization of β-blocker therapy and addition of intravenous amiodarone followed by oral maintenance dosing is required in most cases to abort and prevent recurrent ventricular arrhythmia.…”
Section: Benefits Of Adjuvant Antiarrhythmic Drug Therapymentioning
confidence: 99%
“…The most often causes in the background of 20% of ES are electrolyte disorders, stress or unexpected proarrhythmia caused by antiarrhythmic agents [11,13,21,22].…”
Section: Pathomechanismmentioning
confidence: 99%